Sox7 controls arterial specification in conjunction withhey2andefnb2function - Dorien M. A. Hermkens; Andreas van Impel; Akihiro Urasaki; Jeroen Bussmann; Henricus J. Duckers; Stefan Schulte‐Merker (2015)
SoxF family members have been linked to arterio-venous specification events and human pathological conditions, but in contrast to Sox17 and Sox18, a detailed in vivo analysis of a Sox7 mutant model is still lacking. In this study we generated zebrafish sox7 mutants to understand the role of Sox7 during vascular development. By in vivo imaging of transgenic zebrafish lines we show that sox7 mutants display a short circulatory loop around the heart as a result of aberrant connections between the lateral dorsal aorta (LDA) and either the venous primary head sinus (PHS) or the common cardinal vein (CCV). In situ hybridization and live observations in flt4:mCitrine transgenic embryos revealed increased expression levels of flt4 in arterial endothelial cells at the exact location of the aberrant vascular connections in sox7 mutants. An identical circulatory short loop could also be observed in newly generated mutants for hey2 and efnb2. By genetically modulating levels of sox7, hey2 and efnb2 we demonstrate a genetic interaction of sox7 with hey2 and efnb2. The specific spatially confined effect of loss of Sox7 function can be rescued by overexpressing the Notch intracellular domain (NICD) in arterial cells of sox7 mutants, placing Sox7 upstream of Notch in this aspect of arterial development. Hence, sox7 levels are crucial in arterial specification in conjunction with hey2 and efnb2 function, with mutants in all three genes displaying shunt formation and an arterial block.